2010
DOI: 10.1111/j.1471-0528.2010.02491.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of pre‐eclampsia by an analysis of placenta‐derived cellular mRNA in the blood of pregnant women at 15–20 weeks of gestation

Abstract: Objective A panel of cellular mRNA markers was used to predict the occurrence of pre-eclampsia in pregnant women at 15-20 weeks of gestation.Design Prospective cohort study.Setting The Department of Obstetrics and Gynaecology, University of Indonesia, Cipto Mangunkusumo National Hospital, Indonesia.Sample Peripheral blood samples from asymptomatic pregnant women.Methods Among 660 women, 62 developed pre-eclampsia at later gestation (pre-eclampsia group) and each case was matched with five controls. Therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 34 publications
0
28
1
Order By: Relevance
“…11 We have previously shown that the mRNA concentrations of HO-1 and SOD are decreased in the cellular component of the maternal blood of pregnant women with preeclampsia, 13 and that these mRNA levels are decreased in the cellular component during the first and early second trimester of women who subsequently developed preeclampsia. 14,15 In the present study, the expression levels of both genes increased significantly with gestational age from 6 to 11 weeks. Remodeling of the spiral arteries probably begins in the early first trimester and is completed by 18 to 20 weeks of gestation, although the exact gestational age at which trophoblast invasion of these arteries ceases is unclear.…”
Section: Discussionmentioning
confidence: 60%
“…11 We have previously shown that the mRNA concentrations of HO-1 and SOD are decreased in the cellular component of the maternal blood of pregnant women with preeclampsia, 13 and that these mRNA levels are decreased in the cellular component during the first and early second trimester of women who subsequently developed preeclampsia. 14,15 In the present study, the expression levels of both genes increased significantly with gestational age from 6 to 11 weeks. Remodeling of the spiral arteries probably begins in the early first trimester and is completed by 18 to 20 weeks of gestation, although the exact gestational age at which trophoblast invasion of these arteries ceases is unclear.…”
Section: Discussionmentioning
confidence: 60%
“…As stated above, the preeclampsia risk associated to these two proteins concentrations is known, but there is inconsistent data regarding plasmatic changes of their mRNA at the end of the first trimester of pregnancy, when preeclampsia screening can be performed. Two studies mentioned lower values for PIGF mRNA in pregnancies destined to develop preeclampsia (19,20) and we found no study to evaluate PAPP-A mRNA changes in maternal plasma at an early gestational age in cases consequently complicated by preeclampsia.…”
Section: Introductionmentioning
confidence: 50%
“…They obtained a multivariate predictive model that allowed preeclampsia prediction at a sensitivity of 88.7% at a false-positive rate of 10%. Sekizawa et al (19) assessed the early changes in maternal whole blood and predictive value of certain placental transcripts involved in placental angiogenesis and oxidative stress (P-selectin, PLAC1, Flt1, endoglin, HO-1 and PIGF) at the same gestational age. They noticed higher levels of P-selectin, PLAC1, Flt1 and endogline, and lower levels for HO-1 and PIGF in pregnancies complicated by preeclampsia and reported a detection rate of 84% at a false positive rate of 5%.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we reported aberrant expression of some circulating placentalspecific mRNAs (including Flt-1) in maternal blood in preeclampsia cases compared with control participants, and this seemed to be a promising tool for the early detection of the disease. [16][17][18] We could detect patients who would develop preeclampsia based on mRNA level earlier than could be detected by protein level. Some other studies suggested that a high level of soluble Flt-1 in second trimester was associated with FGR.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] In the previous studies, we were able to detect patients who would develop preeclampsia by examining the mRNA level earlier than by examining the protein level. [16][17][18] Although it is not clear evidence that mRNAs offer advantages over protein markers, a molecular analysis has the advantage of being able to evaluate a large number of markers at the same time and to provide useful information about disease pathophysiology. The alterations in expression of these molecules have led to the proposal that they may be used as early predictive markers of preeclampsia and/or FGR before onset of clinical symptoms.…”
Section: Introductionmentioning
confidence: 99%